Pengaruh Komunikasi Interpersonal Guru Sejarah Kebudayaan Islam Terhadap Motivasi Belajar Siswa - Amelia, Dina; Yudhyarta, Deddy Yusuf (Asatiza: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the effect of interpersonal communication of Islamic cultural history teachers on the learning motivation of class IX.4 students at Madrasah Tsanawiyah Negeri 2 Indragiri Hilir. The research method with a quantitative approach uses data collection techniques, namely questionnaires and documentation. While the data analysis technique uses a simple regression analysis formula. The population in this study were all students of class IX.4, totaling 36 students. The results showed that the effect of interpersonal communication on teachers of Islamic cultural history reached 64.32% and the influence of student learning motivation reached 60.73%. There was also the effect of interpersonal communication on teachers of Islamic cultural history on student learning motivation in class IX.4 which is indicated by F. count ≥ F table, then Ho is rejected, meaning it is significant, namely F count 10.43 ≥ F table 4.13, then Ho is rejected, and Ha is accepted.